Some chemical constituents isolated from Acorus tatarinowii Shott - Dung, Nguyen The; Hong Van, Nguyen Thi; Ty, Pham Dinh; Taylor, W. C. (Vietnam Journal of Chemistry, 2014)
Anew 8,1′-neolignan, tatarinone, 4-[2-(1,2,3-trimethoxybenz-5-yl)-1-methylethyl]-2,5-dimethoxy-4-(2-propenyl)-2,5-cyclohexadien-1-one, has been isolated from Acorus tatarinowii rhizome and  its structure determined by spectroscopic methods, including 2D-NMR spectra. Asarylaldehyde and a mixture of α-asarone and β-asarone were also isolated and  indentified.Keywords: Acorus tatarinowii;Araceae; 8,1′-neolignans; asarylaldehyde; α-asarone; β-asarone; NMR.